2012
DOI: 10.1080/10941665.2011.627352
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Theory of Planned Behavior and Motivation: An Exploratory Study of Potential Beach-based Resorts in Vietnam

Abstract: The decision-making process of travel destination choice is very complex. Understanding why people travel and what factors influence tourists' travel intentions has been paid much attention by tourism scholars. This study attempted to examine the predictive power of theory of planned behavior (TPB) with the addition of past behavior and travel motivation in predicting behavioral intention of choosing a beach-based resort in Vietnam. Data were collected in three cities in both northern and southern Vietnam from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 41 publications
6
45
1
4
Order By: Relevance
“…Ferguson and Bibby (2002) studied the relation between the blood donor's past behavior and future intention of blood donating, and then make a conclusion that behavior intention can be predicted by accidental behaviors and past behaviors. Chien et al (2012) has also demonstrated the relation between past behavior and behavioral intention. Furthermore, an inverted U-shaped curve relation exists between the past behavior and future behavior, especially for the regular blood donors.…”
Section: A Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferguson and Bibby (2002) studied the relation between the blood donor's past behavior and future intention of blood donating, and then make a conclusion that behavior intention can be predicted by accidental behaviors and past behaviors. Chien et al (2012) has also demonstrated the relation between past behavior and behavioral intention. Furthermore, an inverted U-shaped curve relation exists between the past behavior and future behavior, especially for the regular blood donors.…”
Section: A Hypothesesmentioning
confidence: 99%
“…In order to facilitate for tourists to co create experience value then, not only should the industry recognize experiences that tourists value but should also acknowledge motivation and involvement as essential in value creation for tourist experiences (Chien et al 2012). Attitude and tourist value link subjective norm, Perceived behavioral control, past behavior and image of tourism destination together.…”
Section: B Attitude and Tourist Value Are Both Important Mediate Varmentioning
confidence: 99%
See 1 more Smart Citation
“…It may then branch into Pearce's hierarchal travel career steps, or travel ladder, (Scarinci & Richins, 2008;Chang, 2007;Chien et al, 2012), or the concept of "push and pull" factors (Chan & Baum, 2007;Chang, 2007;Chien et al, 2012;Gnoth, 1997). Other studies use the Plog's travel personality or Cohen's work on "strangeness" vs. "familiarity" when covering tourist motivations to travel (Chen, Mak, & McKercher, 2011).…”
Section: Motivational Theoriesmentioning
confidence: 99%
“…Most motivation literature in consumer behavior and tourism studies starts with Maslow's hierarchy of needs as a theoretical foundation (Chang, 2007;Chien, Yen, & Hoang, 2012;Kozak, 2002).…”
Section: Motivational Theoriesmentioning
confidence: 99%